A Techno-Economic Analysis of Widespread Microgrid/Minigrid Deployment in Pakistan’s Electrical Power Sector (The Pakistan Development Review, 2025)
In the recent past, the Government of Pakistan has undertaken certain appreciable initiatives in the electrical power sector, which is undergoing an extensive reform and restructuring process, particularly in the areas of decarbonisation and deregulation. Although Pakistan is blessed with abundant natural energy resources, a significant percentage of the population remains without electricity access since the expansion of the centralised grid is uneconomical due to certain reasons, including but not limited to limited financial resources and a scattered population. In this regard, micro/mini-grid (MG) deployment offers an excellent opportunity to address this problem, improve the life quality of the people of Pakistan, and help improve the economy. The study is predominately based on simulation and analysis-based research methods wherein the techno-economic analysis is performed keeping in view the technical and commercial aspects and also MG impacts on Pakistan’s power grid and prospective customers of MGs. According to this study’s findings, in comparison to fossil fuel-based MGs, renewable energy-dominated MGs offer a lucrative investment opportunity/financial viability and also contribute to reducing adverse effects on the environment. Even though MGs present a costeffective solution for the remote unelectrified areas of Pakistan, they may suffer from technical issues if not properly designed. Direct current MGs and the application of MGs for irrigation purposes present interesting cases with respect to reducing the overall cost of energy. Some of the important factors to be considered to evaluate the feasibility of MGs are the electricity demand pattern, supply reliability requirement, discount rate, and project lifetime, among other things. There is an urgent need for a comprehensive policy and regulatory framework since the existing one is insufficient to effectively upscale MGs deployment in Pakistan. While assessing electricity provision options for remote unelectrified areas of Pakistan, the electricity planners must consider and evaluate MGs before proposing huge investments in transmission and distribution infrastructure. One of the important considerations is to align the design of MGs with the affordability for the customers in each specific geographical area, to create a win-win situation for all the stakeholders.